Kepemimpinan Kepala Madrasah Berbasis Kecerdasan Emosional dalam Membangun Kemitraan - Noni Nimas Ariyanti; Nur Ittihadatul Ummah (Universitas Islam Kiai Haji Achmad Siddiq Jember, 2022)
Leadership based on emotional intelligence is the ability to regulate and manage emotions. Leaders who have emotional intelligence will involve the ability to manage emotions so they can direct their emotions in a positive direction. With guidance from an emotionally intelligent leader, someone will feel comfortable, making it easier to build partnerships. Conversely, without good emotional intelligence, leaders will struggle to build partnerships. This study aims to determine emotional intelligencebased leadership on personal competence aspects and social competence aspects of madrasah directors in building partnerships. Data collection techniques use interviews, observation and documentation. Data analysis used the qualitative data analysis of the interactive model of Miles, Hubarman and Saldana. Validity of data uses triangulation of sources and techniques. The results of this study are as follows: 1) the leadership of the madrasah director based on emotional intelligence in the aspect of personal competence shows that the leaders have self-awareness and are able to manage them. 2) The leadership of madrasah managers based on emotional intelligence in the aspect of social competence in building partnerships shows that madrasah managers have a social conscience and have the ability to manage relationships by building partnerships with parents through discussion forums (Forsafi), partnerships with agencies/institutions include partnerships with: (Global Institute's Training Education and Courses), CV. Indah Permatasari, BPR East Java, At-tartil, Al-Falah Social Fund Foundation (YDSF), Ummi Foundation, Balaidesa, Puskesmas and the community. Kepemimpinan berbasis kecerdasan emosional adalah sebuah kemampuan mengatur dan mengelola emosi. Pemimpin yang memiliki kecerdasan emosional akan melibatkan kemampuan mengelola emosi sehingga bisa mengarahkan emosinya ke arah yang positif. Dengan bimbingan pemimpin yang cerdas secara emosi akan membuat seseorang merasa nyaman sehingga memudahkan dalam menjalin kemitraan. Begitupun sebaliknya, tanpa kecerdasan emosional yang baik maka pemimpin akan sulit membangun kemitraan. Penelitian ini bertujuan untuk mengetahui kepemimpinan berbasis kecerdasan emosional pada dimensi kompetensi pribadi maupun dimensi kompetensi sosial kepala madrasah dalam membangun kemitraan. Teknik pengumpulan data dengan wawancara, observasi dan dokumentasi. Analisis data menggunakan analisis data kualitatif model interaktif Miles, Hubarman dan Saldana. Keabsahan data dengan triangulasi sumber dan teknik. Hasil penelitian ini adalah: 1) Kepemimpinan Kepala Madrasah berbasis kecerdasan emosional pada dimensi kompetensi pribadi menunjukkan bahwa pemimpin memiliki kesadaran diri dan mampu mengelola diri. 2) Kepemimpinan Kepala Madrasah berbasis kecerdasan emosional pada dimensi kompetensi sosial dalam membangun kemitraan menunjukkan bahwa kepala madrasah memiliki kesadaran sosial dan memiliki kemampuan pengelolaan relasi dengan membangun kemitraan dengan orang tua melalui forum diskusi (Forsafi), kemitraan dengan instansi/lembaga meliputi kemitraan dengan: (Pendidikan Pelatihan dan Kursus Global Institute), CV. Indah Permatasari, BPR Jatim, At-tartil, Yayasan Dana Sosial Al-Falah (YDSF), Ummi Foundation’s, Balaidesa, Puskesmas dan masyarakat